0588 Effect of CPAP Therapy on Depressive Symptoms. (27th April 2018) - Zamora, T; Stepnowsky, C J
Abstract: Introduction: Obstructive Sleep Apnea (OSA) is a medical condition characterized by partial or complete cessation of breath during sleep. There is much overlap between OSA and depression. Some studies have found that CPAP therapy can help reduce depressive symptoms. We had the opportunity to explore this relationship in a large dataset. Methods: Data from three completed clinical trials on continuous positive airway pressure (CPAP) therapy adherence were examined (total n = 649). Baseline Apnea-Hypopnea Index (AHI) was obtained from diagnostic sleep testing. Depressive symptoms were assessed using a self-report measure (Center for Epidemiologic Studies Depression Scale; CESD-10), with higher scores indicating greater severity of depressive symptoms. It was administered at baseline and follow-up visit. Change in CESD was calculated by follow-up minus baseline, such that negative values indicate reductions in depressive symptoms. Results: There was no baseline difference in age, AHI, or body mass index (BMI) between the groups. Baseline CESD-10 was 10.9 ± 7.0 and follow-up was 7.9 ± 5.9. Nightly CPAP adherence measured over the follow-up period was 3.0 ± 2.7 vs. 3.2 ± 2.0 hours per night for Usual Care and Intervention groups, respectively. Change in depressive symptoms was significantly associated with CPAP adherence (r=-0.12; p =.012). Improvement was also seen in measures of sleepiness and quality of life. Conclusion: Treatment of OSA with CPAP therapy can help decrease depressive symptoms. Identification of OSA and consideration of CPAP therapy should be an important consideration for those with clinically significant levels of depressive symptoms. Support (If Any): VA HSR&D IIR 12–069 & VA CSR&D PULM 028-12F.